Investigating Students` Cognitive Style and Problem Solving Skills in Conducting Undergraduate Final Year Project - Gusau, Muhammad Baba; Mohamad, Mimi Mohaffyza; Yusof , Yusmarwati; Ahmad , A (Online Journal for TVET Practitioners, 2019)
Cognitive style was found to be related to problem solving skills including final year project in the majority of studies, field-independent students were found to be superior to field-dependent students. The present study investigated the students` cognitive style and problem-solving skills among final year students. Student’s cognitive style and problem solving in fundamentally different ways, particularly problems requiring conceptual understanding and complicated strategies such as final year project problems. The objectives of this research are to identify students’ cognitive styles and problem solving skills also to investigate the relationship of both variables related to students’ conducting undergraduate final year project. 347 final year students involved in this research. The GEFT questionnaires and problem solving based on IDEAL Model are research instruments used. The result showed that students are more independent of cognitive style and be able to identify the problem in problem skills context. There is no relationship between cognitive style and problem solving skill found even though the importance of both factors being discussed in previous research. Furthermore, researcher is indebted to make some possible suggestions that will enhance and connect student cognitive styles and problem-solving skills, this are; educational focus should not necessarily be on who has/does not have a particular ability, but on how to capitalize on individual strengths, and how to develop learning potential, a better understanding of cultural, social or experiential factors that affect students’ research activities are, thus, critical for enhancement of their active learning through undergraduate research.